2010
DOI: 10.3389/fneur.2010.00151
|View full text |Cite
|
Sign up to set email alerts
|

The importance of systemic response in the pathobiology of blast-induced neurotrauma

Abstract: Due to complex injurious environment where multiple blast effects interact with the body parallel, blast-induced neurotrauma is a unique clinical entity induced by systemic, local, and cerebral responses. Activation of autonomous nervous system; sudden pressure increase in vital organs such as lungs and liver; and activation of neuroendocrine–immune system are among the most important mechanisms that contribute significantly to molecular changes and cascading injury mechanisms in the brain. It has been hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 69 publications
(78 reference statements)
6
150
0
Order By: Relevance
“…All methods that could facilitate a good translation to clinical data (serological biomarkers, neurophysiolgy and imaging) are recommended. Dr. Ibolja Cernak has shown that blast TBI can be a systemic reaction to blast (Cernak, 2010). General inflammatory reactions from the primary blast can contribute to the reactions of the brain.…”
Section: Preclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…All methods that could facilitate a good translation to clinical data (serological biomarkers, neurophysiolgy and imaging) are recommended. Dr. Ibolja Cernak has shown that blast TBI can be a systemic reaction to blast (Cernak, 2010). General inflammatory reactions from the primary blast can contribute to the reactions of the brain.…”
Section: Preclinicalmentioning
confidence: 99%
“…The propagation of pressure waves through the body in blast trauma is still a subject of disagreement. Important data can be retrieved by carefully planned experiments utilizing incomplete body protection (Cernak, 2010). The importance of repeated mild TBI for development of late development of neurodegenerative disease has been documented in sports medicine (Guskiewicz et al, 2005) and repeated injuries will undoubtedly be included in a number of protocols for research on blast TBI.…”
mentioning
confidence: 99%
“…The surge in catecholamine levels in the brain also may have a relation to inflammation. 64 It has been shown by Cernak 65 that there is a systemic inflammatory response to blast and that this includes the brain. Interestingly, no effects on monoamine transmitter levels were seen in the PFC, in spite of the fact that PFC is a key region in cognition and emotions.…”
Section: Tbi and Monoamine Turnovermentioning
confidence: 99%
“…[13][14][15] An approach to screen mechanisms in a blast TBI model at the threshold of detectible neuropathology could provide useful insight into therapeutic targets. Clues as to possible secondary injury mechanisms after experimental blast TBI were first provided by Cernak and colleagues, 10 who reported on a role for oxidative stress (OS) and neuroinflammation, 16 but studies are limited.…”
mentioning
confidence: 99%